2020
DOI: 10.26434/chemrxiv.12894800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Domain-specific Fingerprints Generated Through Neural Networks to Enhance Ligand-based Virtual Screening.

Abstract: Molecular fingerprints are essential for different cheminformatics approaches like similarity-based virtual screening. In this work, the concept of neural (network) fingerprints in the context of similarity search is introduced in which the activation of the last hidden layer of a trained neural network represents the molecular fingerprint. The neural fingerprint performance of five different neural network architectures was analyzed and compared to the well-established Extended Connectivity Fingerprint (ECFP)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…DNNs found many use cases in molecular virtual screening and de novo compound generation (Figure 1) [19]. This rapidly evolving class of algorithms has been influencing modern drug discovery by building more accurate QSAR models [12,23], creating better molecular representations [24][25][26], predicting 3D protein structure with impressive accuracy [27] or achieving other promising results in many medicinal and clinical applications [3,12,17,21,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…DNNs found many use cases in molecular virtual screening and de novo compound generation (Figure 1) [19]. This rapidly evolving class of algorithms has been influencing modern drug discovery by building more accurate QSAR models [12,23], creating better molecular representations [24][25][26], predicting 3D protein structure with impressive accuracy [27] or achieving other promising results in many medicinal and clinical applications [3,12,17,21,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we showed that these neural networks can also be used to generate target-specific fingerprints implicitly incorporating target relevant information. [12] A similar approach was chosen by Stojanović and colleagues [13] who trained a Graph Neural Network to predict the binding of molecules to a specific protein target. Fingerprints were extracted for a new dataset and it could be shown that these neural fingerprints outperformed traditional ones.…”
Section: Introductionmentioning
confidence: 99%
“…DNNs found many use cases in molecular virtual screening and de novo compound generation (Figure 1) [19]. This rapidly evolving class of algorithms has been influencing modern drug discovery by building more accurate QSAR models [12,23], creating better molecular representations [24][25][26], predicting 3D protein structure with impressive accuracy [27] or achieving other promising results in many medicinal and clinical applications [3,12,17,21,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%